Trends in the external business environment for banking activity in Iraq (Entrepreneurship Journal for Finance and Business, 2021)
The research aims to demonstrate the importance of the economic business environment and the restrictions imposed on banks in general that may limit banking activity. Banks have to analyze the environment in which they intend to work in order to know these restrictions and analyze them in order to be able to adapt to them. Without banks analyzing that environment, they will not be able to continue their activities, .The research problem arises in highlighting trends that restrict banking activity in Iraq, and this will be done through three sections .The first introduced a profile of business environment in Iraq, while the second investigated the main features of the banking system .As for the third topic, it includes an assessment of the banking activities in light of the general economic business environment. Relevant Indicators showed that there are external variables inherent in the general business environment that affect banking activity both directly and indirectly.